Classification of Transcription Boundary-Associated RNAs (TBARs) in Animals and Plants - Yu, Dongliang; Ma, Xiaoxia; Zuo, Ziwei; Wang, Huizhong; Meng, Yijun (Frontiers in Genetics, 2018)
There is increasing evidence suggesting the contribution of non-coding RNAs (ncRNAs) to the phenotypic and physiological complexity of organisms. A novel ncRNA species has been identified near the transcription boundaries of protein-coding genes in eukaryotes, bacteria, and archaea. This review provides a detailed description of these transcription boundary-associated RNAs (TBARs), including their classification. Based on their genomic distribution, TBARs are divided into two major groups: promoter-associated RNAs (PARs) and terminus-associated RNAs (TARs). Depending on the sequence length, each group is further classified into long RNA species (>200 nt) and small RNA species (<200 nt). According to these rules of TBAR classification, divergent ncRNAs with confusing nomenclatures, such as promoter upstream transcripts (PROMPTs), upstream antisense RNAs (uaRNAs), stable unannotated transcripts (SUTs), cryptic unstable transcripts (CUTs), upstream non-coding transcripts (UNTs), transcription start site-associated RNAs (TSSaRNAs), transcription initiation RNAs (tiRNAs), and transcription termination site-associated RNAs (TTSaRNAs), were assigned to specific classes. Although the biogenesis pathways of PARs and TARs have not yet been clearly elucidated, previous studies indicate that some of the PARs have originated either through divergent transcription or via RNA polymerase pausing. Intriguing findings regarding the functional implications of the TBARs such as the long-range "gene looping" model, which explains their role in the transcriptional regulation of protein-coding genes, are also discussed. Altogether, this review provides a comprehensive overview of the current research status of TBARs, which will promote further investigations in this research area.